Improvement of Steady State Performance of Voltage Control in Switched Reluctance Generator: Experimental Validation - Zeineb Touati; Manuel Pereira; Rui Esteves Araújo; Adel Khedher (Machines, 2022)
This paper presents a voltage control approach to a Switched Reluctance Generator (SRG) using a Proportional Integral (PI) controller. The principle of operation is described and the considerations in the design of controller are discussed. A current loop transfer function of an SRG with power converter has been systematically derived in order to obtain a small-signal model for the generator. The generated voltage is controlled by manipulation of the setpoint of the current control of the generator. The entire voltage loop controller and current control have been simulated and tested with a 250 W SRG prototype. The control law of the control system was implemented on a digital signal processor (TMS320F28379D). To verify the feasibility of the proposed voltage control, the performances are evaluated by numerical simulations and experimental tests with an 8/6 SRG for different rotational speeds and resistive loads. Experimental results demonstrate that the DC output voltage from SRG can be controlled well using a simple linear controller.